A rare case of large isolated internal iliac artery aneurysm with ureteral obstruction and hydronephrosis: Compression symptoms are limitation for endovascular procedures. (April 2015) - Nenezic, Dragoslav; Tanaskovic, Slobodan; Gajin, Predrag; Ilijevski, Nenad; Novakovic, Aleksandra; Radak, Djordje
Introduction: In this report, we aim to present a rare case of isolated internal iliac artery aneurysm with associated left ureteric obstruction and consequent hydronephrosis. Case report: A 66-year-old male patient was admitted for occasional pain in the lower back that appeared one month earlier. CT arteriography revealed isolated internal iliac artery (diameter 99 mm) with ureteral obstruction, hydroureter and left kidney hydronephrosis occurrence. Aneurysm was resected, after six months the patient was doing well. Bearing in mind that 77% of the patients with isolated internal iliac artery have symptoms caused by aneurysmal compression on adjacent organs, we wanted to highlight that despite the amazing expansion of endovascular procedures in the last decades, its therapeutic effect in isolated internal iliac artery's treatment is to a great extent limited since compression symptoms cannot be solved. Conclusion: Open surgery remains the gold standard for isolated internal iliac artery's treatment considering significant limitations of endovascular procedures due to the inability to eliminate problems caused by compression.